Dinamika Kepribadian dalam Perspektif Sigmund Freud dan Psikologi Islami - Eni Rakhmawati (La-Tahzan: Jurnal Pendidikan Islam, 2022)
Humans are very complex creatures so that psychological scientists want to reveal the secrets that exist in humans, because each individual certainly has a different character. Personality is an understanding of behavior, thoughts, feelings, and parts of the soul that build human existence into a unity that is not separated in carrying out its functions. Therefore, personality is defined as understanding the I, the self, the self, or understanding the whole human being. In Islam, the term personality (syakhshiyah) is used to describe a person's behavior and try to assess its good and bad. Sigmund Freud concluded that the human self in forming his personality consists of 3 main components namely id, ego and superego. human personality according to Islamic psychology has three components, lust (Al-Nafs), reason (Al-Aql) and heart (Al-Qalb). Personality is actually a product of the interaction between the three components, it's just that there is one that dominates over the other components. The dynamics of human personality in the perspective of Islamic Psychology include: First, mutma'innah personality (serene principle). Second, lawwamah personality (awareness principle). Third, ammarah personality (pleasure principle). The typology of personality in Islam, which comes from the Qur'an and Sunnah, is divided into: First, the believer type. Second, the disbeliever type. Third, the hypocrite type.